Mathematical Analysis of Age-Structured Susceptibility in Campylobacteriosis Transmission Dynamics - Ahmed, Karim K.; Yusuf, Jibrin Sale; Aliyu, Aliyu Isa; Agaie, Baba Galadima; Ozsahin, Ilker; Sulaiman, Tukur Abdulkadir; Khalifa, Abeer S. (Springernature, 2025)
Campylobacteriosis remains one of the leading causes of bacterial gastroenteritis worldwide, particularly affecting children and adults through contaminated food and water sources. This study develops and analyzes an age-structured mathemati-cal model for Campylobacteriosis transmission that incorporates mild and severe infection classes, as well as treatment and public awareness interventions. The total population is stratified into child and adult groups with age-dependent susceptibil-ity. The basic reproduction number, R-0, is derived using the next-generation matrix method and serves as a threshold parameter governing disease persistence. Analytical results reveal that the disease-free equilibrium is locally and globally asymptotically stable when R-0<1, and unstable otherwise. Sensitivity analysis identifies the transmission rates (beta) and awareness rate (u1) as the most influential parameters affecting disease spread. Numericalsimulations, performed using the fourth-order Runge-Kutta scheme in Maple 2024, demonstrate that the combined implementation of public awareness and treatment efforts under optimal control significantly reduces the infection burden. The study highlights that simultaneous awareness and treatment interventions are more effective than either control applied individually. These results provide quantitative insights for designing targeted public health strategies aimed at mitigating Campylobacteriosis transmission across age groups.
Keywords: Campylobacteriosis disease; Epidemiology; Age structure